FILSAFAT PENDIDIKAN ISLAM DAN TAMENG MORALITAS BANGSA - Fathurrizqi Almubarok; Nabila Herlin; Nurul Mubin (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This article examines the irrational behavior patterns exhibited by educated individuals, particularly in relation to corrupt actions. It is crucial to recognize that moral education cannot be compromised, as the fundamental mission of education is to cultivate a noble humanitarian spirit, elevating individuals beyond mere physical existence and transient concerns. There exists a flaw within the educational framework in Indonesia, which fails to ensure that the personal conduct of educated individuals remains virtuous. This article provides an analysis and critique of the prevailing perception of education as it is practiced in Indonesia. The methodology employed in this article is grounded in the philosophy of Islamic education, which articulates the philosophical underpinnings of education as understood within the context of Islam. This philosophical overview is deemed suitable for investigating human moral behavior. The findings of this research aim to bolster national integrity and protect the nation from the pervasive moral crisis that is currently widespread.